Residential Time Spent and Homicide during the COVID-19 Pandemic - Cubukcu, Suat; Darcan, Emirhan; Aksu, Gokhan (International Journal of Criminology and Sociology, 2023)
The United States has witnessed a significant upsurge in homicide rates during the COVID-19 pandemic (NCHS, 2021). While multiple theories attempt to account for this increase, our study examines the impact of changes in human mobility resulting from stay-at-home and social distancing measures on variations in homicide incidents. We conducted a fixed-effects Poisson regression analysis using panel data that encompasses the day of the week and week collected from Chicago between February 2020 and July 2021. Our findings indicate that the increased time spent in residential settings due to stay-at-home orders is not a significant factor in explaining the rise in homicide numbers. Instead, our study suggests that the pandemic as a whole and its influence on individual strains provide a more plausible explanation for the increase in homicide incidence.